PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA FLASH CARD PADA MATA PELAJARAN IPAS SISWA KELAS lV SD NEGERI WUKIRSARI - Melisa Permata Sari; Syaprizal; Tiogustisatria (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was conducted to examine the effect of applying the Problem Based Learning (PBL) model supported by flash card media on the Science and Social Studies (IPAS) learning outcomes of fourth-grade students at SD Negeri Wukirsari, particularly on the topic of Indonesia's Cultural Diversity. The research adopted a quantitative approach using a Pre-Experimental Design with a One Group Pretest-Posttest Design. The participants consisted of all students in the fourth grade of SD Negeri Wukirsari, who served as both the population and the research sample. Data were obtained through a learning achievement test comprising 16 valid multiple-choice items that had previously met the criteria of validity, reliability, item difficulty, and discrimination index. The collected data were then analyzed using the Chi-Square normality test and the t-test to test the research hypothesis. The findings revealed an improvement in students' learning outcomes after the learning model was implemented. The average pre-test score was 50.85, while the average post-test score increased to 80.11. The results of the Chi-Square normality test indicated that both the pre-test and post-test scores were normally distributed. In addition, the hypothesis testing using the t-test confirmed that the implementation of the Problem Based Learning (PBL) model assisted by flash card media significantly influenced students' learning outcomes in Science and Social Studies (IPAS). Based on these findings, it can be concluded that the use of the Problem Based Learning (PBL) model supported by flash card media contributed significantly to improving the Science and Social Studies (IPAS) learning outcomes of fourth-grade students at SD Negeri Wukirsari on the topic of Indonesia's Cultural Diversity.